(untitled) (Mustansiria Dental Journal, 2005)
The aim of study was to evaluate the effect ofthe number of pregnancy in the dental health of iraqi women . Three hundred ninety nine pregnant women were included in this study, with an age range of 18-39 years old. They were attending to the Maternal and Child Health Care Center (MCHCC) for their monthly periodic checkup with different pregnancy stages. The sample of the study was randomly selected from four out of 16 MCHCCs in the center of Mosul city . Caries experience were diagnosed and recorded according to the criteria suggested by WHO 1997 using CPI probe. The (DMFS) index was used to assess the decayed, missing and filled surfaces . The periodontal health status of pregnant women was performed using the following clinical parameters (gingival index, plaque index and calculus index .) To evaluate the effective of number of pregnancy on dental health status, the sample divided into three group (1-3) according to the number of pregnancy (1-3, 4-6 , )75 respectively . The result indicated an increase in the mean of DMF S score with an increase in the number of pregnancy; also the study indicates a significant increase in the mean of periodontal parameters with an increase in the number of pregnancy